Digital transformation and green innovation synergy: double drivers for global value chain upgrading in China's construction machinery industry - Xia, Weifu; Alwie, Aryaty; Taasim, Shairil Izwan; Jin, Wong Tze; Naning, Fatin Hana (Creative Publishing House, 2024)
With the digital transformation of the global economy and the deepening of the concept of sustainable development, China's construction machinery industry faces major opportunities and challenges in the reconstruction and upgrading of the global value chain. Based on the dynamic capability theory and the collaborative innovation theory, this study constructs a theoretical framework of "digital transformation-green innovation-global value chain upgrading" to explore the impact of the synergy between digital transformation and green innovation on improving the position of Chinese construction machinery companies in the global value chain. This study uses a multi-source data fusion method, combined with patent data, financial statements and questionnaires, to construct an unbalanced panel data set of 189 listed construction machinery companies in China from 2010 to 2022, and uses econometric methods such as dynamic panel modeling, threshold regression and machine learning to analyze. The study finds that: (1) The impact of digital transformation on the global value chain upgrading of construction machinery companies presents a nonlinear "U-shaped" curve relationship; (2) Green innovation plays a positive regulatory role in the relationship between digital transformation and value chain upgrading; (3) There is a significant synergy between digital transformation and green innovation; (4) The quality of the institutional environment has an important impact on the synergy, and a high-quality institutional environment enhances the synergy; (5) Enterprise heterogeneity significantly moderates the impact of synergy on value chain upgrading. The study expands the theory of global value chains, enriches the theory of collaborative innovation, provides a new theoretical perspective for the integration of digital economy and green development, and provides practical guidance for enterprises and governments to formulate relevant strategies and policies. Future research can further explore the cross-national comparison and long-term dynamic evolution of synergy effects.